The Impact of Knowledge Sharing and Integrity on Work Productivity Mediated by Organizational Commitment Variables - Nur Ainun Nafilah; Supriyono Supriyono; Agus Prayitno; Kusni Ingsih (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
The aim of this research is to develop a model of the relationship between knowledge sharing, integrity, organizational commitment and work productivity of Bank Contact Center employees. The research respondents consisted of 150 employees who worked in banking in the Contact Center section. Primary data was obtained by distributing questionnaires via Google Form. Data analysis uses the Structural Equation Model method with the SmartPLS application version 3.0. Three stages of testing were held: measurement model testing, structural model testing, and indirect effect testing. The research results show that knowledge sharing and integrity have a positive and significant effect on organizational commitment and work productivity. Organizational commitment partially mediates the effect of knowledge sharing and integration on work productivity.